Caught in Geopolitical Fragmentation: How to De-risk Germany's Economic Model - Sebastian de Quant; Sander Tordoir; Shahin Vallée (Forum for a New Economy, 2024)
Stagnating globalisation, the possible weaponisation of dependencies by autocracies, and US-China tensions threaten to disrupt Germany's export-driven economic model. But German efforts to 'derisk' that model remain underdeveloped, as does its policy toolkit. Germany's most important trade relationship is with China. Germany's import, export and investment exposure to an increasingly mercantilist and possibly aggressive China pose considerable risk to its comparative advantage and security. But the range of policy-levers required to address these- such as export controls or industrial policy - needs upgrading. Given Germany's deep integration into the European economy, they also need to be defined much more consistently across the state, federal, and EU level. Successfully managing China-related risks can serve as a template for an integrated EU de-risking policy toolkit to make Germany's model more resilient. – – Die stagnierende Globalisierung, die mögliche Ausnutzung von Abhängigkeiten durch Autokratien und die Spannungen zwischen den USA und China drohen das exportorientierte deutsche Wirtschaftsmodell ins Wanken zu bringen. Die deutschen Bemühungen, die Risiken dieses Modells zu "entschärfen", sind ebenso wie die möglichen Instrumente noch unterentwickelt. Die wichtigste Handelsbeziehung Deutschlands ist die mit China. Importe, Exporte und Investitionen in ein zunehmend merkantilistisches und möglicherweise aggressiv agierendes China stellen daher ein erhebliches Risiko für die deutsche Sicherheit dar und drohen den komparativen Vorteil Deutschlands zu schmälern. Um diesen Risiken zu begegnen, ist eine Erweiterung des politischen Instrumentariums - etwa der Exportkontrolle oder der Industriepolitik - dringend erforderlich. Angesichts der starken Verflechtung Deutschlands mit der europäischen Wirtschaft müssen die Maßnahmen nicht nur auf Bundes- und Landesebene, sondern auch auf EU-Ebene wesentlich kohärenter definiert werden. Ein erfolgreiches Risikomanagement im Umgang mit China könnte als Vorbild für ein integriertes europäisches De-Risking-Instrumentarium dienen und das deutsche Modell langfristig widerstandsfähiger machen.
Keywords: F13; F14; F21; F51; F33; F68; L52; O52; 330; Geoeconomics; International trade; De-risking; Germany-China relations; European Union; Industrial policy